Titanium-based solid electrolyte materials

KR103032503B1Active Publication Date: 2026-10-13OTSUKA CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020237018334
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-04
Filing Date
2021-11-15
Publication Date
2026-10-13
Estimated Expiration
2041-11-15

Smart Images

  • Figure 112023059842445-PCT00001_ABST
    Figure 112023059842445-PCT00001_ABST
Patent Text Reader

Abstract

A titaniumate-based solid electrolyte material is provided that has no concern regarding the generation of hydrogen sulfide, does not contain rare earth elements, and has good lithium ion conductivity. The titaniumate-based solid electrolyte material is characterized by comprising a lepidocrosite-type titaniumate having a structure in which a plurality of host layers are stacked, wherein octahedra formed by six-coupling oxygen atoms to titanium atoms are linked in a two-dimensional direction by edge sharing, and lithium ions are arranged between the layers of said host layers, wherein a portion of the titanium sites in the host layers are substituted with monovalent to trivalent cations.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a titanium acid-based solid electrolyte material. Background Technology

[0002] A lithium-ion rechargeable battery consists of a positive electrode, a negative electrode, a separator that prevents physical contact between the positive and negative electrodes, and an electrolyte. Charging and discharging are performed by lithium ions moving between the positive and negative electrodes through the electrolyte. Due to their excellent energy and power densities, as well as their effectiveness in miniaturization and weight reduction, lithium-ion rechargeable batteries are used as power sources for laptops, tablets, and smartphones. They are also attracting attention as power sources for electric vehicles.

[0003] Conventional electrolytes use liquids containing flammable organic solvents, which makes leakage prone and poses a risk of ignition due to short circuits occurring inside the battery during overcharging and discharging. Therefore, in recent years, research and development of all-solid-state lithium-ion secondary batteries using inorganic solid electrolyte materials instead of liquid electrolytes has been conducted to improve safety.

[0004] Inorganic solid electrolyte materials used in all-solid-state lithium-ion secondary batteries are classified into two types: sulfide-based solid electrolyte materials and oxide-based solid electrolyte materials, based on whether the main element forming the framework is an oxygen atom or a sulfur atom. Sulfide-based solid electrolyte materials exhibit higher lithium-ion conductivity compared to oxide-based solid electrolyte materials, but they have high reactivity with moisture and pose safety issues such as the generation of hydrogen sulfide. Therefore, (La,Li)TiO3 (hereinafter referred to as "LLTO"), Li6La2CaTa2O 12 , Li6La2ANb2O 12 (A=Ca,Sr), Li2Nd3TeSbO 12Methods to improve the lithium ion conductivity of oxide-based solid electrolyte materials are being investigated. For example, a method of doping LLTO with 1 mass% to 5 mass% of sulfur is disclosed (see Patent Document 1). Prior art literature

[0005] Japanese Patent Publication No. 2018-73805 The problem to be solved

[0006] However, the oxide-based solid electrolyte material of Patent Document 1 is at risk of generating hydrogen sulfide because it contains sulfur. In addition, there is also a concern regarding manufacturing costs because it uses rare earth elements.

[0007] The objective of the present invention is to provide a titanium acid-based solid electrolyte material that has no risk of hydrogen sulfide generation, does not contain rare earth elements, and has good lithium ion conductivity, a method for manufacturing the same, and a solid electrolyte and a lithium ion secondary battery using the said titanium acid-based solid electrolyte material. means of solving the problem

[0008] The present invention provides the following titanium acid-based solid electrolyte material, a method for manufacturing the same, a solid electrolyte, and a lithium-ion secondary battery.

[0009] A titanium-based solid electrolyte material characterized by comprising a lepidocrosite-type titaniumate having a structure in which a plurality of host layers are stacked such that octahedra formed by six-fold oxygen atoms to titanium atoms are linked in a two-dimensional direction by edge sharing, and lithium ions are arranged between the layers of said host layers, wherein a portion of the titanium sites in said host layers are substituted with monovalent to trivalent cations.

[0010] Claim 2 A titanium acid-based solid electrolyte material as described in Claim 1, wherein the interlayer distance of the host layer is 5 Å or more and 10 Å or less.

[0011] Claim 3 The lepidocrosite-type titaniumate described in Claim 1 or Claim 2 having crystal water is a titanium-based solid electrolyte material.

[0012] Claim 4 A titanium acid-based solid electrolyte material described in any one of Claims 1 to 3, wherein the content of lithium ions present between the layers of the host layer is 45 mol% or more and 100 mol% or less with respect to 100 mol% of ions present between the layers of the host layer.

[0013] A titanium acid-based solid electrolyte material described in any one of claims 1 to 4, wherein the compound represented by the following general formula (1) and at least one of the compounds represented by the following general formula (2).

[0014] Li x M I y Ti 1.73 O 3.7 내지 4 ·nH2O … Equation (1)

[0015] [During the meal, M I represents alkali metals excluding lithium, where the exponent x is 0.3 to 1.0, the exponent y is 0 to 0.4, and the exponent n is 0 to 2.

[0016] Li x M I y M II z Ti 1.6 O 3.7 내지 4 ·nH2O … Equation (2)

[0017] [During the meal, M I is an alkali metal excluding lithium, M II represents alkaline earth metals, and the exponent x is 0.3 to 1.0, the exponent y is 0 to 0.4, the exponent z is 0 to 0.4, and the exponent n is 0 to 2.]

[0018] A method for manufacturing a titanium acid-based solid electrolyte material as described in any one of claims 1 to 5, comprising the steps of mixing a lepidocrosite-type titanium salt and a lithium salt and heat treating.

[0019] A method for manufacturing a titanium acid-based solid electrolyte material as described in any one of claims 1 to 5, comprising the steps of mixing a lepidocrosite-type titanium salt and an acid to prepare a lepidocrosite-type titanium acid, and mixing the lepidocrosite-type titanium acid and a lithium salt.

[0020] A solid electrolyte having a titanium acid-based solid electrolyte material as described in any one of claims 1 to 5.

[0021] A lithium-ion secondary battery having the solid electrolyte described in claim 9 of claim 8. Effects of the invention

[0022] According to the present invention, a titanium acid-based solid electrolyte material can be provided that has no risk of hydrogen sulfide generation, does not contain rare earth elements, and has good lithium ion conductivity. By using a solid electrolyte having this titanium acid-based solid electrolyte material, a high-output battery with excellent safety can be obtained. Brief explanation of the drawing

[0023] FIG. 1 is a schematic diagram illustrating a titanium acid-based solid electrolyte material according to one embodiment of the present invention. FIG. 2 is a schematic cross-sectional view showing a lithium-ion secondary battery according to one embodiment of the present invention. Figure 3 is a Nyquist plot of Examples 1 to 4 and Comparative Example 1. Figure 4 is the Nyquist plot of Examples 1, 5, and 6. Specific details for implementing the invention

[0024] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiment is merely an example. The present invention is not limited in any way to the following embodiment.

[0025] Titanium-based solid electrolyte materials

[0026] The titanium acid-based solid electrolyte material of the present invention is characterized by comprising a lepidocrosite-type titaniumate having a structure in which a plurality of host layers are stacked, wherein octahedra formed by six-fold oxygen atoms to titanium atoms are linked in a two-dimensional direction by edge sharing, and lithium ions are arranged between the layers of said host layers, wherein a portion of the titanium sites in the host layers are substituted with monovalent to trivalent cations, and said lepidocrosite-type titaniumate may or may not have crystal water between the layers of the host layers, etc. Preferably, said lepidocrosite-type titaniumate has crystal water between the layers of the host layers, etc.

[0027] The host layer is formed by octahedrons in which oxygen atoms are 6-foldly coupled to titanium atoms, which are linked in a two-dimensional direction through edge sharing, and forms a single layer that serves as a stacking unit. Originally, each individual host layer is electrically neutral, but it carries a negative charge because some of the tetravalent titanium sites are substituted with monovalent to trivalent cations or are vacant. The electrical neutrality of this compound is maintained by being compensated by positive charges, such as lithium ions, existing between the host layers (hereinafter referred to as "interlayers").

[0028] More specifically, FIG. 1 is a schematic diagram illustrating a titanium acid-based solid electrolyte material according to one embodiment of the present invention. As shown in FIG. 1, the titanium acid-based solid electrolyte material (1) has a crystal structure in which a plurality of host layers (2) are stacked and ions (3), such as lithium ions, are arranged between the layers of the host layers (2). Each host layer (2) is formed by an octahedron in which oxygen atoms are six times coupled to titanium atoms, which is formed in a two-dimensional direction by sharing edges. Furthermore, FIG. 1 is a schematic diagram as an example, and the titanium acid-based solid electrolyte material of the present invention is not limited to the structure of FIG. 1.

[0029] In order to further enhance lithium ion conductivity, it is preferable that among the titanium sites of the host layer, titanium sites exceeding 0 mol% and 40 mol% or less are substituted with monovalent to trivalent cations. Examples of cations include hydrogen ions, oxonium ions, alkali metal ions, alkaline earth metal ions, zinc ions, nickel ions, copper ions, iron ions, aluminum ions, gallium ions, manganese ions, etc. In order to further enhance lithium ion conductivity, it is preferable that at least one is selected from the group consisting of hydrogen ions, oxonium ions, lithium ions, and magnesium ions, and it is more preferable that it be lithium ions or magnesium ions.

[0030] Some of the titanium sites in the host layer may be vacancies, and if vacancies are present, it is preferable that the titanium sites in the host layer have more than 0 mol% and 15 mol% or less of vacancies in order to further increase lithium ion conductivity.

[0031] The interlayer distance of the host layer of the lepidocrosite-type titaniumate constituting the titaniumate-based solid electrolyte material is preferably 5 Å or more, more preferably 6 Å or more, preferably 10 Å or less, more preferably 9 Å or less, and even more preferably 7 Å or less. The lepidocrosite-type titaniumate has a layered structure within its crystal structure and exhibits lithium ion conductivity as the interlayers serve as two-dimensional conduction paths for lithium ions. It is believed that by setting the interlayer distance to the above range, the lithium ion density between layers can be increased, the activation energy of ion conduction is low, and the lithium ion conductivity is further improved.

[0032] In the X-ray diffraction pattern, several peaks appearing at equal intervals in the low-angle region (approximately 2θ = 20° or less) originate from the layered structure of titanium dioxide, and the interlayer distance can be calculated from the diffraction angle (2θ) of the first peak appearing on the lowest angle side. Specifically, it can be calculated using Bragg’s formula “d = nλ / 2sinθ” (where d is the interlayer distance (Å), θ is the value obtained by dividing the diffraction angle (2θ) of the first peak by 2, λ is the wavelength of the CuKα line, 1.5418 Å, and n is a positive integer (n=1 in the case of the first peak).

[0033] In the interlayers of the host layer, only lithium ions may be disposed, or, provided that the desirable physical properties of the present invention are not impaired, hydrogen ions, oxonium ions, alkali metal ions, alkaline earth metal ions, etc. may be disposed in addition to lithium ions, and from the viewpoint of further increasing lithium ion conductivity, it is preferable that at least one type selected from the group consisting of hydrogen ions, oxonium ions, potassium ions, and sodium ions be disposed. In the interlayers of the host layer, it is more preferable that potassium ions or sodium ions are disposed in addition to lithium ions. The content of lithium ions present in the interlayers of the host layer is preferably 45 mol% or more, more preferably 60 mol% or more, even more preferably 80 mol% or more, preferably 100 mol% or less, and more preferably 90% or less, with respect to 100 mol% of ions present in the interlayers of the host layer, from the viewpoint of further increasing lithium ion conductivity.

[0034] Lepidocrosite-type titaniumates constituting titanium-based solid electrolyte materials are powder particles with shapes such as spherical (including those with slight irregularities on the surface or those with a cross-sectional shape that is approximately spherical, such as elliptical), columnar (including those with a rod shape, cylindrical, prismatic, rectangular, approximately cylindrical, or approximately rectangular shape, etc., in which the overall shape is approximately columnar), plate-like, block-like, a shape having multiple convex parts (amoeba-like, boomerang-like, cross-like, star-shaped candy-like, etc.), and irregular shapes. The particle size is not particularly limited, but it is preferable that the average particle diameter is 0.01 μm to 20 μm, more preferable that it is 0.05 μm to 10 μm, and even more preferable that it is 0.1 μm to 5 μm.

[0035] In this specification, "average particle size" refers to the particle size at 50% cumulative based on the cumulative standard in the particle size distribution obtained by the laser diffraction and scattering method (particle size at 50% cumulative based on volume), i.e., D 50It refers to the (median diameter), and the cumulative 50% particle size based on this volume (D 50 ) is the particle size at the point where the cumulative value reaches 50% by counting the number of particles starting from the smallest particle size on a cumulative curve in which the particle size distribution is calculated based on volume and the total volume is set to 100%. These various particle shapes and particle sizes can be arbitrarily controlled by the shape of the lepidocrosite-type titaniumate that serves as the raw material, which will be described later.

[0036] As for the lepidocrosite-type titaniumate described above, at least one of the compounds represented by the following general formula (1) and the compounds represented by the following general formula (2) is preferred, and Li 0.3 내지 1.1 K 0 내지 0.1 Na 0 내지 0.5 Ti 1.73 O 3.7 내지 4 ·0 to 2H2O, Li 0.3 내지 1.1 K 0 내지 0.5 Ti 1.73 O 3.7 내지 4 ·0 to 2H2O, Li 0.3 내지 1.6 K 0 내지 0.1 Mg 0 내지 0.4 Ti 1.6 O 3.7 내지 4 At least one compound selected from the group consisting of ·0 to 2H2O is more preferable, and Li 0.5 내지 1.1 K 0 내지 0.1 Na 0 내지 0.5 Ti 1.73 O4·O to 2H2O, Li 0.5 내지 1.1 K 0 내지 0.1 Ti 1.73 O4·O to 2H2O, Li 0.5 내지 1.6 K 0 내지 0.1 Mg 0 내지 0.4 Ti 1.6 At least one compound selected from the group consisting of O4·O to 2H2O is more preferable, and Li 0.5 내지 1.1 K 0 내지 0.1 Ti 1.73 O4·0.1 to 2H2O, Li 0.5 내지 1.6 K 0 내지 0.1 Mg 0 내지 0.4 Ti 1.6At least one compound selected from the group consisting of O4·0.1 to 2H2O is particularly preferred.

[0037] Li x M I y Ti 1.73 O 3.7 내지 4 ·nH2O … Equation (1)

[0038] [During the meal, M I represents alkali metals excluding lithium, where the exponent x is 0.3 to 1.1, the exponent y is 0 to 0.4, and the exponent n is 0 to 2.

[0039] Li x M I y M II z Ti 1.6 O 3.7 내지 4 ·nH2O … Equation (2)

[0040] [During the meal, M I is an alkali metal excluding lithium, M II represents alkaline earth metals, and the exponent x is 0.3 to 1.6, the exponent y is 0 to 0.4, the exponent z is 0 to 0.4, and the exponent n is 0 to 2.]

[0041] The exponent x of general formula (1) is 0.3 to 1.1, preferably 0.5 to 1.1, and more preferably 0.7 to 1.1. The exponent x of general formula (2) is 0.3 to 1.6, preferably 0.5 to 1.6, and more preferably 0.7 to 1.1.

[0042] The exponent y of general formula (1) is 0 to 0.4, preferably 0.05 to 0.35, and more preferably 0.05 to 0.1. The exponent y of general formula (2) is 0 to 0.4, preferably 0.01 to 0.1.

[0043] The exponent z of general formula (2) is 0 to 0.4, and preferably 0.2 to 0.35.

[0044] The exponent n of general formula (1) is 0 to 2, preferably 0.1 to 2. The exponent n of general formula (2) is 0 to 2, preferably 0.1 to 2.

[0045] The titanium acid-based solid electrolyte material of the present invention is suitable for use as a solid electrolyte material for lithium-ion secondary batteries due to its excellent lithium-ion conductivity and lack of sulfur content. Furthermore, since it does not contain sulfur, there is no concern regarding the generation of hydrogen sulfide, and it is superior in terms of manufacturing cost as it does not use rare earth elements.

[0046] (Method for manufacturing titanate-based solid electrolyte material)

[0047] The titanium acid-based solid electrolyte material of the present invention is not limited to a specific manufacturing method as long as the above composition can be achieved, but an example of a manufacturing method characterized by reacting a lithium salt with a lepidocrosite-type titanium salt or a lepidocrosite-type titanium acid may be given.

[0048] A manufacturing method for reacting a lithium salt with a lepidocrosite-type titanium salt includes a process (I) of mixing a lepidocrosite-type titanium salt and a lithium salt, which are raw materials, and heat-treating them. In the mixing process (I), it is preferable to also mix a potassium salt or a sodium salt to further increase lithium ion conductivity.

[0049] In process (I), the lepidocrosite-type titaniumate that serves as the raw material (hereinafter also simply referred to as "raw material titaniumate") is A x M y Ti (2-y) O4 [wherein A is one or more alkali metals excluding Li, M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, Mn, x is a number from 0.5 to 1.0, and y is a number from 0.25 to 1.0], A 0.5 내지 0.7 Li 0.27Ti 1.73 O 3.85 내지 3.95 [In the formula, A is one or more alkali metals excluding Li], A 0.2 내지 0.7 Mg 0.40 Ti 1.6 O 3.7 내지 3.95 [In the formula, A is one or more alkali metals excluding Li], A 0.5 내지 0.7 Li (0.27-x) M y Ti (1.73-z) O 3.85 내지 3.95 Examples include [wherein A is one or more alkali metals excluding Li, M is one or more selected from Mg, Zn, Ga, Ni, Cu, Fe, Al, and Mn (provided that in the case of two or more types, ion combinations of different valencies are excluded), x and z are x=2y / 3 and z=y / 3 when M is a divalent metal, x=y / 3 and z=2y / 3 when M is a trivalent metal, and y is 0.004≤y≤0.4], and preferably A 0.5 내지 0.7 Li 0.27 Ti 1.73 O 3.85 내지 3.95 [In the formula, A is one or more alkali metals excluding Li] and A 0.2 내지 0.7 Mg 0.40 Ti 1.6 O 3.7 내지 3.95 [In the formula, A is at least one selected from the group consisting of one or more alkali metals excluding Li].

[0050] The lithium salt used in process (I) has a lower melting point than the raw titanium salt and melts at the heat treatment temperature of process (I). Examples include lithium nitrate, lithium chloride, lithium sulfate, lithium carbonate, etc., and preferably lithium nitrate.

[0051] When using a sodium salt in process (I), the sodium salt has a lower melting point than the raw titanium salt and melts at the heat treatment temperature of process (I), and sodium nitrate can be used as an example.

[0052] When using a potassium salt in process (I), the potassium salt has a lower melting point than the raw titanium salt and melts at the heat treatment temperature of process (I), and potassium nitrate can be used as an example.

[0053] The amount of the mixture of lithium salt, a salt compound of lithium and potassium salt, or a salt compound of lithium and sodium salt is preferably 10 to 30 equivalents with respect to the exchangeable cation capacity of the raw titanium salt. If it is less than 10 equivalents, sufficient ion exchange cannot be expected, and if it exceeds 30 equivalents, it is not economically advantageous. "Exchangeable cation capacity" refers, for example, to layered titanium salt of general formula A x M y Ti (2-y) In the case where it is expressed as O4 [wherein A is one or more alkali metals excluding Li, M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, Mn, x is a number from 0.5 to 1.0, and y is a number from 0.25 to 1.0], it refers to the value expressed as x.

[0054] In process (I), a raw titanium salt is mixed with a lithium salt, a salt compound of a lithium salt and a potassium salt, or a salt compound of a lithium salt and a sodium salt, and heat-treated so that the raw titanium salt reacts with the lithium salt or the salt compound while maintaining the layered structure of the raw titanium salt, thereby producing a lepidocrosite-type titanium salt constituting the solid electrolyte material of the present invention. This mixing is preferably performed under dry conditions, and the heat treatment conditions may be, for example, a temperature range of 250°C to 350°C, preferably 250°C to 300°C, for 24 to 72 hours. After heat treatment, the salt compound, which is a flux component, is washed away with deionized water and dried to form the lepidocrosite-type titanium salt constituting the solid electrolyte material of the present invention.

[0055] A manufacturing method for reacting a lithium salt with lepidocrosite-type titanium acid comprises a process (II) for preparing lepidocrosite-type titanium acid by mixing a raw material lepidocrosite-type titanium salt and an acid, and a process (III) for mixing the lepidocrosite-type titanium acid prepared in process (II) with a lithium salt. In the mixing process (III), it is preferable to also mix a potassium salt or a sodium salt to further increase lithium ion conductivity.

[0056] In process (II), the raw titanium salt is mixed with an acid (acid treatment). It is preferable that the acid treatment be performed under wet conditions. Through this acid treatment, the cations, such as metal ions that substitute a portion of the titanium sites in the host layer and metal ions between the host layers, are replaced with hydrogen ions or hydronium ions while maintaining the layered structure of the raw titanium salt, thereby making it lepidocrosite-type titanium acid. The titanium acid referred to here includes hydrated titanium acid in which water molecules exist between the layers.

[0057] The acid used in process (II) is not particularly limited and may be an inorganic acid such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, or boric acid, or an organic acid. Acid treatment can be performed, for example, by mixing the acid into an aqueous slurry of the raw titaniumate, and the treatment temperature is preferably 5°C to 80°C. The cation exchange rate can be controlled by appropriately adjusting the type and concentration of the acid and the concentration of the raw titaniumate slurry depending on the type of raw titaniumate, but the cation exchange rate is preferably 70% to 100% relative to the exchangeable cation capacity of the raw titaniumate in terms of the interlayer distance of the obtained lepidocrosite-type titaniumate. "Exchangeable cation capacity" refers, for example, to layered titaniumate of general formula A x M y Ti (2-y)When expressed as O4 [wherein A is one or more alkali metals excluding Li, M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, Mn, x is a number from 0.5 to 1.0, and y is a number from 0.25 to 1.0], it refers to the value expressed as x+my when the valence of M is m.

[0058] In process (III), the lithium salt is mixed with the lepidocrosite-type titanium acid prepared in process (II) (lithiation treatment), thereby causing the lithium salt to undergo an ion exchange reaction with interlayer hydrogen ions, hydronium ions, etc. In the lithiation treatment, it is preferable to also mix a potassium salt or a sodium salt to further increase lithium ion conductivity. The lithiation treatment is preferably performed under wet conditions, and after this lithiation treatment, the material can be dried and a solvent such as water removed to form the lepidocrosite-type titanium salt constituting the solid electrolyte material of the present invention. After process (III), further heat treatment may be performed. Examples of heat treatment conditions include 0.5 hours to 5 hours at a temperature range of 200°C to 400°C.

[0059] The lithium salt used in process (III) can be one that can introduce lithium ions between the layers of lepidocrosite-type titanium acid, and examples include lithium hydroxide monohydrate, lithium carbonate, lithium acetate, lithium citrate, lithium chloride, lithium nitrate, lithium sulfate, lithium phosphate, lithium bromide, lithium iodide, lithium tetraborate, LiPF6, LiBF4, etc., and preferably lithium hydroxide monohydrate.

[0060] When a sodium salt is used in process (III), the sodium salt may be capable of introducing sodium ions between the layers of lepidocrosite-type titanium acid, and examples include sodium hydroxide, sodium carbonate, sodium acetate, sodium citrate, sodium chloride, sodium nitrate, sodium sulfate, sodium phosphate, sodium bromide, sodium iodide, sodium tetraborate, NaPF6, NaBF4, etc., and preferably sodium hydroxide. These may be used alone or in combination.

[0061] When using a potassium salt in process (III), the potassium salt may be capable of introducing potassium ions between the layers of lepidocrosite-type titanium acid, and examples include potassium hydroxide, potassium carbonate, potassium acetate, potassium citrate, potassium chloride, potassium nitrate, potassium sulfate, potassium phosphate, potassium bromide, potassium iodide, potassium tetraborate, KPF6, KBF4, etc., and preferably potassium hydroxide. These may be used alone or in combination.

[0062] In process (III), in order to react a lithium salt, a salt compound of a lithium salt and a potassium salt, or a salt compound of a lithium salt and a sodium salt with lepidocrosite-type titanium acid, the lithium salt or salt compound is mixed directly, or the lithium salt or salt compound is diluted in water or an aqueous medium, with a suspension of lepidocrosite-type titanium acid dispersed in water or an aqueous medium, and the mixture is stirred. The amount of lithium salt or salt compound mixed is preferably 0.2 to 3 equivalents of the lithium salt or salt compound relative to the exchangeable cation capacity of the lepidocrosite-type titanium acid, and more preferably 1 to 2 equivalents. If it is less than 0.2 equivalents, sufficient ion exchange cannot be expected, and if it exceeds 3 equivalents, it is not economically advantageous. "Exchangeable cation capacity" refers to, for example, a layered titanium salt of general formula A x M y Ti (2-y)When expressed as O4 [wherein A is one or more alkali metals excluding Li, M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, Mn, x is a number from 0.5 to 1.0, and y is a number from 0.25 to 1.0], it refers to the value expressed as x+my when the valence of M is m.

[0063] Solid Electrolyte

[0064] The solid electrolyte of the present invention is a solid electrolyte composed of the titanium acid-based solid electrolyte material described above, and is a layer capable of conducting lithium ions without containing a flammable organic solvent.

[0065] The proportion of solid electrolyte material included in the solid electrolyte is preferably 10 volume% to 100 volume%, more preferably 50 volume% to 100 volume%, with respect to 100 volume% of the total amount of solid electrolyte. The solid electrolyte may contain a binder that binds the particles of the solid electrolyte material.

[0066] The thickness of the solid electrolyte is preferably 0.1 μm to 1000 μm, more preferably 0.1 μm to 300 μm.

[0067] Methods for forming a solid electrolyte include, for example, sintering a solid electrolyte material or manufacturing a solid electrolyte sheet containing a binder. As the binder, materials similar to those described below for the binders used in the positive and negative electrodes may be used. Furthermore, in order to avoid altering the crystal structure during sintering, it is preferable to set the sintering temperature lower than the heat treatment temperature used when manufacturing the solid electrolyte material.

[0068] The solid electrolyte of the present invention is suitable for use as a solid electrolyte for lithium-ion secondary batteries due to its excellent lithium-ion conductivity and lack of sulfur content. Furthermore, since it does not contain sulfur, there is no concern regarding the generation of hydrogen sulfide, and it is superior in terms of manufacturing cost as it does not use rare earth elements.

[0069] Battery

[0070] The battery of the present invention is a lithium-ion secondary battery having a positive electrode, a negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode, wherein the solid electrolyte is a titanium acid-based solid electrolyte material of the present invention, i.e., an all-solid-state battery.

[0071] More specifically, FIG. 2 is a schematic cross-sectional view showing a lithium-ion secondary battery according to one embodiment of the present invention.

[0072] As illustrated in FIG. 2, a lithium-ion secondary battery (10) comprises a solid electrolyte (11), a positive electrode (12), and a negative electrode (13). The solid electrolyte (11) has a first main surface (11a) and a second main surface (11b) facing each other. The solid electrolyte (11) is composed of a solid electrolyte containing the titanium acid-based solid electrolyte material of the present invention. A positive electrode (12) is stacked on the first main surface (11a) of the solid electrolyte (11). A negative electrode (13) is stacked on the second main surface (11b) of the solid electrolyte (11).

[0073] The method for manufacturing the battery of the present invention is not particularly limited as long as it is a method capable of obtaining the battery described above, and a method similar to known battery manufacturing methods may be used. For example, a manufacturing method may be provided in which a power generation element is produced by sequentially pressing and stacking a positive electrode, a solid electrolyte, and a negative electrode, the power generation element is housed inside a battery case, and the battery case is caulked.

[0074] As a battery case used in the battery of the present invention, a general battery case may be used. Examples of battery cases include stainless steel battery cases.

[0075] The battery of the present invention exhibits excellent safety as there is no concern regarding the generation of hydrogen sulfide due to the inclusion of the solid electrolyte of the present invention. Since the lithium ion conductivity is high, the use of a solid electrolyte enables the production of a high-output battery. Furthermore, by including the solid electrolyte, it acts as a separator, eliminating the need for conventional separators and allowing for the expectation of thin-film battery construction.

[0076] Hereinafter, each component of the battery of the present invention will be described.

[0077] (Straight play)

[0078] The positive electrode constituting the battery of the present invention has a positive electrode current collector and a positive electrode active material layer.

[0079] Examples of positive electrode current collectors include copper, nickel, stainless steel, iron, titanium, aluminum, aluminum alloy, etc., and preferably aluminum. The thickness and shape of the positive electrode current collector can be appropriately selected according to the application of the battery, and, for example, may have a strip-shaped planar shape. In the case of a strip-shaped positive electrode current collector, it may have a first surface and a second surface as the back surface thereof. The positive electrode active material layer may be formed on one surface or on both surfaces of the positive electrode current collector.

[0080] The positive electrode active material layer is a layer containing a positive electrode active material, and may contain a conductive material and a binder as needed. The positive electrode active material layer may also contain the solid electrolyte material of the present invention, and by containing the solid electrolyte material of the present invention, it can be made into a positive electrode active material layer with even higher lithium ion conductivity. The thickness of the positive electrode active material layer is preferably 0.1 μm to 1000 μm.

[0081] The positive electrode active material may be any compound capable of absorbing and releasing lithium or lithium ions, for example, lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMnO2), and lithium nickel-cobalt-aluminumate (LiNi 0.8 Co 0.15 Al 0.05 O2, etc.), lithium nickel-cobalt-manganese (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, Li 1+x Ni 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (0≤x<0.3), etc.), spinel oxide (LiM2O4, M=Mn, V), lithium metal phosphate (LiMPO4, M=Fe, Mn, Co, Ni), silicate oxide (Li2MSiO4, M=Mn, Fe, Co, Ni), LiNi 0.5 Mn 1.5 Examples include O4, S8, etc.

[0082] Conductive materials are incorporated to improve current collection performance and to suppress contact resistance between the positive electrode active material and the positive electrode current collector, and examples include carbon-based materials such as vapor-grown carbon fiber (VGCF), coke, carbon black, acetylene black, ketjen black, graphite, carbon nanofiber, and carbon nanotube.

[0083] A binder is formulated to fill the gaps of the dispersed positive electrode active material and to bind the positive electrode active material to the positive electrode current collector, and is, for example, a synthetic material such as polysiloxane, polyalkylene glycol, ethyl-vinyl alcohol copolymer, carboxymethylcellulose (CMC), hydroxypropyrrimethylcellulosepropyl (HPMC), cellulose acetate, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), butadiene rubber, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-ethylene-butadiene-styrene copolymer (SEBS), ethylene-propylene rubber, butyl rubber, chloroprene rubber, acrylonitrile-butadiene rubber, acrylic rubber, silicone rubber, fluororubber, and urethane rubber. Examples include rubber, polyimide, polyamide, polyamideimide, polyvinyl alcohol, and chlorinated polyethylene (CPE).

[0084] As a method for manufacturing a positive electrode, for example, a slurry is prepared by suspending a positive electrode active material, a conductive material, and a binder in a solvent, and this slurry is applied to one or both sides of a positive electrode current collector. Subsequently, the applied slurry is dried to obtain a laminate of a positive electrode active material-containing layer and a positive electrode current collector. After that, a method of pressing the laminate can be given as an example. In another method, the positive electrode active material, the conductive material, and the binder are mixed, and the resulting mixture is formed into pellets. Subsequently, a method of placing these pellets on a positive electrode current collector can be given as an example.

[0085] (Polar)

[0086] The negative electrode constituting the battery of the present invention has a negative electrode current collector and a negative electrode active material layer.

[0087] Examples of negative electrode current collectors include stainless steel, copper, nickel, carbon, etc., and preferably copper. The thickness and shape of the negative electrode current collector can be appropriately selected according to the application of the battery, and, for example, may have a strip-shaped planar shape. In the case of a strip-shaped current collector, it may have a first surface and a second surface as the back surface thereof. The negative electrode active material layer may be formed on one surface or on both surfaces of the negative electrode current collector.

[0088] The negative electrode active material layer is a layer containing a negative electrode active material, and may contain a conductive material and a binder as needed. The negative electrode active material layer may also contain the solid electrolyte material of the present invention, and by containing the solid electrolyte material of the present invention, it can be made into a negative electrode active material layer with even higher lithium ion conductivity. The thickness of the negative electrode active material layer is preferably 0.1 μm to 1000 μm.

[0089] Examples of negative electrode active materials include metal active materials, carbon active materials, lithium metal, oxides, nitrides, or mixtures thereof. Examples of metal active materials include In, Al, Si, Sn, etc. Examples of carbon active materials include mesocarbon micro beads (MCMB), highly oriented graphite (HOPG), hard carbon, soft carbon, etc. Examples of oxides include Li4Ti5O 12 Examples include the like. As for nitrides, LiCoN, etc.

[0090] Conductive materials are incorporated to improve current collection performance and to suppress contact resistance between the negative electrode active material and the negative electrode current collector, and examples include carbon-based materials such as vapor-grown carbon fiber (VGCF), coke, carbon black, acetylene black, ketjen black, graphite, carbon nanofiber, and carbon nanotube.

[0091] A binder is formulated to fill the gaps of the dispersed negative electrode active material and to bind the negative electrode active material and the negative electrode current collector, and is, for example, polysiloxane, polyalkylene glycol, polyacrylic acid, carboxymethylcellulose (CMC), hydroxypropyrrimethylcellulosepropyl (HPMC), cellulose acetate, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), butadiene rubber, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-ethylene-butadiene-styrene copolymer (SEBS), ethylene-propylene rubber, butyl rubber, chloroprene rubber, acrylonitrile-butadiene rubber, acrylic rubber, silicone rubber, fluororubber, and synthetic rubbers such as urethane rubber, polyimide, Examples include polyamide, polyamideimide, polyvinyl alcohol, and chlorinated polyethylene (CPE).

[0092] As a method for manufacturing a negative electrode, for example, a slurry is prepared by suspending a negative electrode active material, a conductive material, and a binder in a solvent, and this slurry is applied to one or both sides of a negative electrode current collector. Subsequently, the applied slurry is dried to obtain a laminate of a negative electrode active material-containing layer and a negative electrode current collector. After that, a method of pressing the laminate can be given as an example. In another method, the negative electrode active material, the conductive material, and the binder are mixed, and the resulting mixture is formed into pellets. Subsequently, an example of a method of placing these pellets on a negative electrode current collector can be given.

[0093] Examples

[0094] The present invention will be described in more detail below based on specific embodiments. The present invention is not limited in any way to the following embodiments, and it is possible to implement it with appropriate modifications within the scope of not altering the gist thereof.

[0095] For the raw titaniumate used in the examples and comparative examples, and the obtained powder, the average particle size was measured by a laser diffraction particle size distribution measuring device (SALD-2100, manufactured by Shimadzu Seisakusho Co., Ltd.), and the interlayer distance was confirmed by analysis using an X-ray diffraction measuring device (Ultima IV, manufactured by Rigaku Co., Ltd.). In addition, the composition formula was confirmed by an ICP-AES analyzer (SPS5100, manufactured by SII Nano Technologies Co., Ltd.) and a thermogravimetric measuring device (EXSTAR6000 TG / DTA6300, manufactured by SII Nano Technologies Co., Ltd.).

[0096] <Raw Titanium Salt>

[0097] The raw titanium salts used in the examples and comparative examples are as follows.

[0098] (Raw Titanium Titanate A)

[0099] As a raw material titaniumate A, lepidocrosite-type lithium potassium titaniumate (K) having potassium ions between layers and lithium ions in the host layer 0.6 Li 0.27 Ti 1.73 O 3.9 ) was used. This lepidocrosite-type lithium potassium titanium dioxide had an average particle size of 3 μm, was a white powder containing plate-like particles, and had an interlayer distance of 7.8 Å.

[0100] (Raw Titanium Titanate B)

[0101] As a raw material titaniumate B, magnesium potassium titanate of the lepidocrosite type having potassium ions between layers and magnesium ions in the host layer (K 0.6 Mg 0.4 Ti 1.6 O 3.9 ) was used. This lepidocrosite-type magnesium potassium titaniumate had an average particle size of 5 μm, was a white powder containing plate-like particles, and had an interlayer distance of 7.8 Å.

[0102] (Example 1)

[0103] 65 g of raw material titaniumate A was dispersed in 1 kg of deionized water, and 50.4 g of 95% sulfuric acid was added. After stirring for 1 hour, the mixture was separated and washed with water. This operation was repeated twice to obtain lepidocrosite-type titanium acid in which some of the potassium and lithium ions were exchanged with hydrogen or hydronium ions. 50 g of this lepidocrosite-type titanium acid was dispersed in 200 g of deionized water, heated to 70°C, and 324 g of a 10% aqueous solution of lithium hydroxide monohydrate was added while stirring. After continuing stirring at 70°C for 3 hours, the mixture was filtered and extracted. After thoroughly washing with hot water at 70°C, the powdered lepidocrosite-type titaniumate was obtained by drying in air at 110°C for 12 hours.

[0104] The average particle size of the obtained lepidocrosite-type titaniumate is 3 µm, the interlayer distance is 8.4 Å, and the compositional formula is K 0.07 Li 1.0 Ti 1.73 It was O4·0.97H2O.

[0105] (Example 2)

[0106] Powdered lepidocrosite-type titaniumate was obtained by heating the lepidocrosite-type titaniumate prepared in Example 1 at 300°C for 1 hour.

[0107] The average particle size of the obtained lepidocrosite-type titaniumate is 3 µm, the interlayer distance is 7.0 Å, and the compositional formula is K 0.07 Li 1.0 Ti 1.73 It was O4·0.21H2O.

[0108] (Example 3)

[0109] 130 g of raw material titaniumate B was dispersed in 1.8 kg of deionized water, and 230.4 g of phosphoric acid was added. After stirring for 1 hour, the mixture was separated and washed with water to obtain lepidocrosite-type titanium acid in which some of the potassium and magnesium ions were exchanged with hydrogen or hydronium ions. This lepidocrosite-type titanium acid was dispersed in 834 g of a 10% aqueous solution of lithium hydroxide monohydrate, heated to 70°C, and stirred. After continuing stirring at 70°C for 3 hours, the mixture was filtered and extracted. After thoroughly washing with hot water at 70°C, the powdered lepidocrosite-type titaniumate was obtained by drying in air at 110°C for 12 hours.

[0110] The average particle size of the obtained lepidocrosite-type titaniumate is 4 µm, the interlayer distance is 8.4 Å, and the compositional formula is K 0.05 Li 1.0 Mg 0.3 Ti 1.6 It was O4·1.1H2O.

[0111] (Example 4)

[0112] 6.0 g of raw titaniumate A and 46 g of lithium nitrate were mixed, and the mixture was heated at 260°C for 48 hours. The sample after heating was washed with water and dried at 110°C for 12 hours to obtain a powdered lepidocrosite-type titaniumate.

[0113] The average particle size of the obtained lepidocrosite-type titaniumate is 3 µm, the interlayer distance is 6.5 Å, and the compositional formula is K 0.09 Li 0.9 Ti 1.73 It was O4·0.13H2O.

[0114] (Example 5)

[0115] 15g of raw titaniumate A was dispersed in 220g of deionized water, and 11.7g of 95% sulfuric acid was added. After stirring for 1 hour, the mixture was separated and washed with water. This operation was repeated twice to obtain lepidocrosite-type titanium acid in which some of the potassium and lithium ions were exchanged with hydrogen or hydronium ions. 5g of this lepidocrosite-type titanium acid was dispersed in 142.5g of deionized water, heated to 40°C, and 0.61g of sodium hydroxide and 1.17g of lithium hydroxide monohydrate were added while stirring. After continuing stirring at 40°C for 3 hours, the mixture was filtered and extracted. After thorough washing, the powdered lepidocrosite-type titaniumate was obtained by drying in air at 110°C for 12 hours.

[0116] The average particle size of the obtained lepidocrosite-type titaniumate is 2 µm, the interlayer distance is 8.7 Å, and the compositional formula is K 0.08 Na 0.28 Li 0.34 Ti 1.73 O 3.8 It was 1.0H2O.

[0117] (Example 6)

[0118] 15g of raw titaniumate A was dispersed in 220g of deionized water, and 11.7g of 95% sulfuric acid was added. After stirring for 1 hour, the mixture was separated and washed with water. This operation was repeated twice to obtain lepidocrosite-type titanium acid in which some of the potassium and lithium ions were exchanged with hydrogen or hydronium ions. 5g of this lepidocrosite-type titanium acid was dispersed in 142.5g of deionized water, heated to 40°C, and 0.81g of potassium hydroxide and 1.17g of lithium hydroxide monohydrate were added while stirring. After continuing stirring at 40°C for 3 hours, the mixture was filtered and extracted. After thorough washing, the powdered lepidocrosite-type titaniumate was obtained by drying in air at 110°C for 12 hours.

[0119] The average particle size of the obtained lepidocrosite-type titaniumate is 2 µm, the interlayer distance is 8.6 Å, and the compositional formula is K 0.30 Li0.43 Ti 1.73 O 3.8 It was 0.84H2O.

[0120] (Comparative Example 1)

[0121] Toshima Seisakusho's Li 0.33 La 0.55 TiO3(cubic)(LLTO) was used as a comparative example. The average particle size was 5㎛.

[0122] Impedance Measurement

[0123] Samples of lepidocrosite-type titaniumates obtained in Examples 1 to 4 and LLTO of Comparative Example 1 were each placed in a Teflon (registered trademark) container having copper electrodes with a diameter of 0.8 cm at both ends, a load of 350 kg / cm² was applied, the thickness of the sample was set to 0.04 cm, and measurements were performed using the AC impedance method in the range of 1 MHz to 1 Hz (measuring device: manufactured by IVIUM Technologies, COMPACTSTAT). The Nyquist plot is shown in FIG. 3.

[0124] 0.050 g of samples of lepidocrosite-type titaniumates obtained in Examples 1, 5, and 6 were each placed in a Teflon (registered trademark) container equipped with copper electrodes with a diameter of 0.8 cm at both ends, a load was applied, pressure was applied to the sample thickness to 1.0 mm, and measurements were performed using the AC impedance method in the range of 1 MHz to 70 Hz (measuring device: manufactured by IVIUM Technologies, COMPACTSTAT). The Nyquist plot is shown in Fig. 4.

[0125] In the Nyquist plot, a semicircular shape is observed on the high-frequency side and a spike shape on the low-frequency side. It is believed that the smaller the semicircle on the high-frequency side, the better the ion conductivity. In FIG. 3, the lepidocrosite-type titaniumates obtained in Examples 1 to 4 all have smaller arcs than the LLTO of Comparative Example 1, indicating that they have superior ion conductivity. Furthermore, in FIG. 4, which shows the results measured under harsher conditions than FIG. 3, the lepidocrosite-type titaniumates obtained in Examples 5 and 6 have smaller arcs than the lepidocrosite-type titaniumates obtained in Example 1. This indicates that sodium ions or potassium ions are additionally arranged between the layers of the host layer, in addition to lithium ions, and thus the ion conductivity is even better. Explanation of the symbols

[0126] 1: Titanium-based solid electrolyte materials 2: Host layer 3: Ions 10: Lithium-ion secondary battery 11: Solid electrolyte 11a: First surrounding 11b: The second face 12: Straight Drama 13: Bu-geuk

Claims

Claim 1 A titanium-based solid electrolyte material characterized by comprising a lepidocrosite-type titaniumate having a structure in which a plurality of host layers are stacked such that octahedra formed by six-fold oxygen atoms to titanium atoms are linked in a two-dimensional direction by edge sharing, and lithium ions are arranged between the layers of said host layers, wherein a portion of the titanium sites in said host layers are substituted with monovalent to trivalent cations. Claim 2 A titanium acid-based solid electrolyte material according to claim 1, wherein the interlayer distance of the host layer is 5 Å or more and 10 Å or less. Claim 3 A titanium acid-based solid electrolyte material according to claim 1 or 2, wherein the lepidocrosite-type titanium salt has crystal water. Claim 4 A titanium acid-based solid electrolyte material according to claim 1 or 2, wherein the content of lithium ions present between the layers of the host layer is 45 mol% or more and 100 mol% or less with respect to 100 mol% of ions present between the layers of the host layer. Claim 5 A titanium acid-based solid electrolyte material according to claim 1 or 2, wherein at least one of the compounds represented by the following general formula (1) and the compounds represented by the following general formula (2). x M I y Ti 1.73 O 3.7 내지 4 ·nH2O … Formula (1)[In the formula, M I Li represents an alkali metal excluding lithium, where the exponent x is 0.3 to 1.0, the exponent y is 0 to 0.4, and the exponent n is 0 to 2.] x M I y M II z Ti 1.6 O 3.7 내지 4 ·nH2O … Formula (2)[In the formula, M I is an alkali metal excluding lithium, M II represents alkaline earth metals, and the exponent x is 0.3 to 1.0, the exponent y is 0 to 0.4, the exponent z is 0 to 0.4, and the exponent n is 0 to 2.] Claim 6 A method for manufacturing a titanium acid-based solid electrolyte material as described in claim 1 or 2, comprising the steps of mixing a lepidocrosite-type titanium salt and a lithium salt and heat treating. Claim 7 A method for manufacturing a titanium acid-based solid electrolyte material as described in claim 1 or 2, comprising the steps of: mixing a lepidocrosite-type titanium salt with an acid to prepare a lepidocrosite-type titanium acid; and mixing the lepidocrosite-type titanium acid with a lithium salt. Claim 8 A solid electrolyte containing the titanium acid-based solid electrolyte material described in claim 1 or 2. Claim 9 A lithium-ion secondary battery having a solid electrolyte as described in paragraph 8.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution battery

    JP2007220406A

  • Negative electrode active material for sodium ion battery, negative electrode for sodium ion battery, and sodium ion battery

    JP2016100058A

  • Ion conductive solid electrolyte compound, method of manufacturing the ion conductive solid electrolyte compound, and electrochemical apparatus having the electrolyte compound

    KR1020200020172A

  • Positive electrode active material for secondary battery and production method therefor, and secondary battery

    WO2017119208A1